2017
DOI: 10.21608/adjalexu.2017.57922
|View full text |Cite
|
Sign up to set email alerts
|

Post-Extraction Socket Preservation With Autogenous Bone Graft and Hyaluronic Acid Followed by Delayed Implant Placement

Abstract: INTRODUCTION:Alveolar ridge atrophy following tooth extraction remains a challenge for future implant placement. Post-extraction socket preservation and implant placement are two methods that are used to prevent significant post-extraction bone loss. OBJECTIVES: The aim of this study was to evaluate the role of hyaluronic acid when mixed with autogenous bone graft in alveolar socket preservation for future implant placement. MATERIALS AND METHODS: A split mouth randomized clinical trial was carried out in 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Also, in 2018, Alcântara et al (33) evaluated the effects of 1% HA gel on bone repair of human dental sockets and observed a significant difference in bone density between the HA-treated sockets and the control groups after 30 days of extraction. Furthermore, our results were also in agreement with Taman et al (31) revealed statistically significant radiographic bone density changes between the two studied groups after 2 months and concluded that hyaluronic acid was more efficient in osteoconduction when compared with autogenous bone graft alone in post-extraction socket preservation. On the contrast, Alcântara et al revealed that HA has no significant difference between the studied groups at 90 days effect of HA when compared the bone density of the extraction sockets using HA gel only (33).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, in 2018, Alcântara et al (33) evaluated the effects of 1% HA gel on bone repair of human dental sockets and observed a significant difference in bone density between the HA-treated sockets and the control groups after 30 days of extraction. Furthermore, our results were also in agreement with Taman et al (31) revealed statistically significant radiographic bone density changes between the two studied groups after 2 months and concluded that hyaluronic acid was more efficient in osteoconduction when compared with autogenous bone graft alone in post-extraction socket preservation. On the contrast, Alcântara et al revealed that HA has no significant difference between the studied groups at 90 days effect of HA when compared the bone density of the extraction sockets using HA gel only (33).…”
Section: Discussionsupporting
confidence: 92%
“…As regarding hyaluronic acid, Taman et al (31) evaluated the effect of hyaluronic acid (HyadentTM) when mixed with autogenous bone graft in alveolar socket preservation, and reported that the ISQ intra-operatively and after 2 months did not affect by hyaluronic acid. Vertical bone height gain increased significantly in each group after 1 and 6 months.…”
Section: Discussionmentioning
confidence: 99%